58.6k views
0 votes
What is the simplest form of this expression?

x - 3/x - 1 + 6/x - 3

A. x^2 + 3/(x - 1)(x - 3)
B. x + 3/(x - 1)(x - 3)
C. x^2 - 6x + 3/(x - 1)(x - 3)
D. x^2 + 12x + 15/(x - 1)(x - 3)

User Alan Bosco
by
4.7k points

1 Answer

3 votes

Answer: x + 3/x -4

Explanation:

(x^2 - 4 x + 3)/x

Roots

x = 1

x = 3

Properties as a real function

Domain

{x element R : x!=0}

Range

{y element R : y<=-2 (2 + sqrt(3)) or y + 4>=2 sqrt(3)}

Derivative

d/dx(x - 3/x - 1 + 6/x - 3) = 1 - 3/x^2

Indefinite integral

integral(-4 + 3/x + x) dx = 1/2 (x - 8) x + 3 log(x) + constant

(assuming a complex-valued logarithm)

Local maximum

max{x - 3/x - 1 + 6/x - 3} = -2 (2 + sqrt(3)) at x = -sqrt(3)

Local minimum

min{x - 3/x - 1 + 6/x - 3} = 2 (sqrt(3) - 2) at x = sqrt(3)

Series representations

-4 + 3/x + x = sum_(n=-∞)^∞ ( piecewise | -4 | n = 0

1 | n = 1

3 | n = -1) x^n

-4 + 3/x + x = sum_(n=-∞)^∞ ( piecewise | 3 (-1)^n | n>1

0 | n = 0

-2 | n = 1) (-1 + x)^n

Definite integral

integral_1^3 (-4 + 3/x + x) dx = log(27) - 4≈-0.704163

What is the simplest form of this expression? x - 3/x - 1 + 6/x - 3 A. x^2 + 3/(x-example-1
User Charmeleon
by
5.0k points